ОРГАНІЗАЦІЯ ГРУПОВОЇ ДІЯЛЬНОСТІ МОЛОДШИХ ШКОЛЯРІВ НА УРОКАХ УКРАЇНСЬКОЇ МОВИ (Педагогіка вищої та середньої школи, 2022)
In the article an author considers notion group work. Accents attention on the types of groups and psychology - pedagogical terms of their unton at junior schoolbayr, determines the tasks on the lessons of Ukrainian for implementation in groups.